Menganalisa Pola Hidup Bersih Sehat ( PHBS ) Dalam Perspektif Islam di Desa Tegalweru Kec. Dau Kabupaten Malang - Ningsih, Anita Andriya; Maulani, Riskiyah; Nurfadillah, Izzah; Aisyah, Tsania Riris Nur (Es-Syajar:Journal of Islam, Science and Technology Integration, 2023)
Clean and Healthy Living Behavior or often abbreviated as PHBS is the behavior or action of seeking cleanliness and health from one's own volition and transmitting it to others. This behavior includes maintaining personal hygiene and health so that it impacts the health of others and the surrounding environment. This research was conducted in Tegalweru Village, Kec. In his environment, Dau Malang Regency found that there are still many public places and local residents who do not understand how to carry out good and correct PHBS. Therefore KKM students carry out socialization related to OHBS in order to create a prosperous society. Implementing PHBS in the community can be said to be difficult considering there is still a lack of awareness within each one. Even though it's not only from health, but religion also often reminds of cleanliness. Because cleanliness is the beginning of a healthy life. If healthy, activities can be carried out including in worshiping God Almighty. The aim of this research is to see how the religious side is related to PHBS. The research method used is descriptive. The results obtained from this study are that religion strongly supports a clean and healthy lifestyle. Even one hadith confirms that cleanliness is part of faith.